Kekerasan Dalam Rumah Tangga di Masyarakat Kontemporer: Kajian Sosiologis terhadap Penyebab dan Dampak Hukumnya - Satriani, Satriani; Rahman R, Abd.; HL, Rahmatiah (Universitas Islam Negeri Alauddin Makassar, 2024)
The main problem in this research is domestic violence in the contemporary era and the legal consequences it causes. In law enforcement, the implementation of investigations basically does not differentiate between the victim and whether the victim must be a wife or husband because in the law it is not called a wife, it is clearly someone who is in the household, be it wife, children, parents, servants or other people. which is under supervision. The availability of sufficient evidence for proof is something that makes things difficult for victims. Forms of domestic violence are not only physical violence, but also sexual and mental violence such as verbal abuse, insults and mental terror if the victim leaves or reports the incident, as well as threats of being killed. As a result, domestic violence victims not only suffer physical injuries but also mental injuries. In this research, normative legal research or library research methods are used. In this normative legal research, library materials are basic data which in research science is classified as secondary data. Secondary data has a very broad scope, including personal letters, legal materials, legal journals, theses, dissertations, views of legal experts or fikhi (doctrine) scholars, diaries, legal books, legal dictionaries, jurisprudence down to official documents issued by the government. The results of this research are that domestic violence occurs due to several factors including economic factors, jealousy, gender inequality, differences in principles, alcohol, promiscuity, lack of good communication, but according to researchers, domestic violence occurs mainly due to lack of education. morals and weak faith in related parties resulting in a lack of implementation of religious values ​​in married life and are easily propagated.